HISTORICAL RECONSTRUCTION OF ARCHITECTURE OF THE ANCIENT PERIOD (ON THE EXAMPLE OF SOUTHERN UZBEKISTAN) - Tog‘ayev J. E. (TARIXIY TADQIQOTLAR, 2025)
This article discusses issues related to the historical reconstruction of Bronze and Early Iron Age architecture. It analyzes reconstruction models of several archaeological sites from the Southern Uzbekistan dating back to these periods and examines the significance of historical reconstruction in the study of ancient architecture.